Financial Positioning Of Commercial Banks And Its Implications To Bank Management - Muda, Muhamad (Asian Academy of Management (AAM), 1996)
The banking system in Malaysia, like many of the banking systems in the developing countries, emerged to facilitate trade transactions either domestically or cross border and as a tool used by the authority to foster the country's economic growth and development through the process of financial intermediation. While market forces influence the development of individual banks, implementation of government policy will mean introduction of regulatory provisions in the banking system that in turn regulates banks activities and determines banking structure. In addition, changes in the capital formation spurred by the active management of the monetary and fiscal policies, have realigned the supply and demand for capital.